AI-enhanced narratives and digital identities: A discourse analysis of personal expressions in social media - Hmood, Saddam S (Research Journal in Advanced Humanities, 2026)
The main goal of this paper is to examine how artificial intelligence on social media platforms impacts the creation of digital identities while also affecting user engagement methods and communication approaches. In order to better understand consumer behavior toward these machine-generated writings, the study also explores how users interact with and react to AI-generated stories when they encounter human interactions as well as how authentic self-expression and personal presentation transform due to technological mediation. Discourse analysis serves as the research method in this study to examine both the linguistic and structural aspects of AI-generated material in addition to its interaction with user-generated discourse on the well-known social media platforms Facebook, Instagram, and Twitter. The selected sites collect user-generated qualitative data to better understand user interactions with AI-generated materials, as well as user responses and the resulting influence on their online communication practices and self-presentation. The research project delivered multiple essential findings, such as AI stories allow users to engage through active participation that transforms the digital identities of those users, but they also create confusion regarding the distinction between machine-made material and human origin, thus opposing established narrative consistency principles. Implications of the research include the fact that the piece stresses that we must rethink standard approaches to the identification of communicative agents when discussing narratives that originate from algorithms. Finally, the analysis provides an original contribution because it analyzes the interface between user-generated texts and AI-generated content to detect the evolution of hybrid online personae.